Amidinyl Radical Formation through Anodic N−H Bond Cleavage and Its Application in Aromatic C−H Bond Functionalization. (9th December 2016) - Zhao, Huai‐Bo; Hou, Zhong‐Wei; Liu, Zhan‐Jiang; Zhou, Ze‐Feng; Song, Jinshuai; Xu, Hai‐Chao
Abstract: We report herein an atom‐economical and sustainable approach to access amidinyl radical intermediates through the anodic cleavage of N−H bonds. The resulting nitrogen‐centered radicals undergo cyclizations with (hetero)arenes, followed by rearomatization, to afford functionalized tetracyclic benzimidazoles in a highly straightforward and efficient manner. This metal‐ and reagent‐free C−H/N−H cross‐coupling reaction exhibits a broad substrate scope and proceeds with high chemoselectivity.